2011
DOI: 10.1007/s10212-011-0083-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning in multiple contexts: are there intra-, cross- and transcontextual effects on the learner’s motivation and help seeking?

Abstract: In Germany, Austria and Switzerland, the majority of 15-19-year olds follow vocational education programmes within a dual-track system, spending most of their time in a company and going to school only 1 day each week. With their separate aims, content and sociological organisation, the company and the school can be considered as two distinct contexts within which apprentices have to acquire the various skills and competencies of their future occupation. In this paper, the development of apprentices' learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 16 publications
4
26
0
4
Order By: Relevance
“…The mechanism of transfer from one context to another in the TCM (e.g., the relationship between autonomous motivation in PE and leisure-time) represents a recognition that educational experiences and accompanying behaviors (e.g., learning about physical exercise that one enjoys in PE) that support autonomy, and therefore likely satisfy psychological needs, lead individuals to seek out like experiences in other contexts particularly if there is congruence between the types of motivation in each context. This alignment and transfer process has also been recognized and supported empirically in other areas (Mata et al, 2009;Pavey & Sparks, 2010;Gurtner et al, 2012).…”
Section: The Tcm Of Motivationmentioning
confidence: 63%
“…The mechanism of transfer from one context to another in the TCM (e.g., the relationship between autonomous motivation in PE and leisure-time) represents a recognition that educational experiences and accompanying behaviors (e.g., learning about physical exercise that one enjoys in PE) that support autonomy, and therefore likely satisfy psychological needs, lead individuals to seek out like experiences in other contexts particularly if there is congruence between the types of motivation in each context. This alignment and transfer process has also been recognized and supported empirically in other areas (Mata et al, 2009;Pavey & Sparks, 2010;Gurtner et al, 2012).…”
Section: The Tcm Of Motivationmentioning
confidence: 63%
“…The dual-track VET system implies that learning emerges from the interaction of multiple contexts (Horn et al 25 2008;Gurtner et al 2012).…”
Section: Different Contexts Different Knowledgementioning
confidence: 99%
“…Differences in motivation in the school and in the company contexts were greater, with for school, the lowest motivation for intrinsic motivation. Gurtner, Gulfi, Genoud, de Rocha Trindade, and Schumacher (2012) studied developments in motivation over three years in students in a dual-track system in Switzerland. Overall, Gurtner et al (2012) found a decline in motivated behaviour (in learning intentions, such as readiness to work hard), motivational beliefs, self-efficacy beliefs and the perceived utility of the learning context.…”
Section: Development In Motivation For School In Students In Senior Smentioning
confidence: 99%